El mejoramiento de la formación educativa de los niños huérfanos de la escuela “Lauro Damerval Ayora nº 1” de la ciudad de Loja, período 2013-2014 - Sarango Valle, Nilda Piedad (2014)
This research work is about: IMPROVING THE EDUCATIONAL TRAINING SCHOOL FOR ORPHANS "Lauro Damerval AYORA No. 1" CITY OF LOJA, PERIOD 2013-2014 CHILDREN which had as general purpose investigate how it affects the orphans in educational training of orphaned children. To do this the importance of school education in their formation was observed, then the causes and consequences that originate orphanhood and finally an alternative proposal for school, in order to improve the teaching of children was developed was investigated. This research is explanatory, applicative and qualitative character. However, within the methods worked with the following: scientific, inductive, deductive and dialectical method. Such techniques as were also used: the survey, the questionnaire applied to the researched community (teachers and students) and observation as a guide; they were also used to obtain truthful and objective information, remain a key issue support tailored to the problems in the school criteria. According to the results we can deduce that the main cause of abandonment is due to the irresponsibility of parents, in addition to living with them is essential to the academic performance of children and this leads to them having to go to work in the streets. The people with whom he worked is formed by six teachers and 32 students. Consequently, it is concluded that aid with orphaned children in their education, by the Ministry of Education is almost zero, or implying that this body has neglected address is important social situation, because if teachers will have training necessary for the proper conduct of the problem, act better; So, your students may feel abandoned their support and coping positively. That is why it is recommended that teachers prepare a methodology for teaching - learning to manage to overcome this problem, leading to many risky situations for children; they can have poor self-esteem, low social status, even depression, this future will bring negative consequences for infants and so may not leave in society and in professional life.